The Influence of Spirituality and Social Status on the Ethical Perceptions of Accountants - M. Azizul Khakim (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to measure and prove that spirituality and social status can affect the ethical perceptions of entrepreneurs. We should understand that humans as social beings are always related to spiritual values, and according to the author, spirituality also influences the views of entrepreneurs. The sample in this study was taken using a data collection method called purposive sampling. The number of samples in the research used was 75 respondents. The data obtained were analyzed using multiple linear regression analysis techniques through SPSS software. The results of the data processing results prove that the influence of these two factors can influence the perceptions of entrepreneurs, and some of them make decisions based on the value of this spirituality.